PERCEIVED QUALITY OF CARE DURING COVID-19 AT SANJIWANI HOSPITAL GIANYAR, BALI - Putu Ayu Indrayathi; Putu Erma Pradnyani; Ni Luh Saptiaryati; Luh Putu Sinthya Ulandari; Laszlo Robert Kolozsvari (OISAA, 2022)
COVID-19 has caused a decrease in the number of visits to health care due to restrictions on public activities to reduce local transmission, but the quality of service is essential to be maintained. This study measured and examined factors related to public satisfaction with the inpatient services provided by Sanjiwani Hospital. This research is an observational study with a cross-sectional design. Of the 204 patients were taken using a consecutive sampling technique. Data collection was conducted from October-November 2020. Data collected of social demographic, 41 questions related to public satisfaction, and six aspects of the prevention of COVID-19. Data were analysed in univariate and bivariate analysis using the T-Test and Oneway Anova to determine factors related to the level of public satisfaction. The results showed general satisfaction score is a value of 4.10, meaning that it is in the satisfied category. There is a trend of increasing public satisfaction scores from 2018 to 2020. The factors related to public satisfaction are based on the type of National Health Insurance (JKN) membership the patient uses during treatment. Sanjiwani hospital should consider establishing digital service innovations to make it easier to access health care in the era of COVID-19.